Analisis Penerapan Model ANJAS GO CLEAR (Aplikasi Normatif Jabatan Struktural Government Clear) Di Kota Bogor - Yeremia Mardut My Lucky; Sulistyowati - - (Journal of Politic and Government Studies, 2020)
The use of information technology encourages the realization of good public services in cities or in areas commonly known as the concept e-Government (Electronic Govrnment). One of the breakthroughs and innovations made by the Bogor City Government is the Normative Application for Structural Government Position - Clear. The first application in Indonesia is called (Anjas Go Clear) which was officially launched by the Civil Service and Apparatus Development Agency (BKPSDA). This policy innovation arises from a major problem related to the mismatch between employee competence and the position occupied. The distribution of employees that is not in accordance with the circumstances and conditions of the real needs of an organization caused by an intervention by a person or group of people to assign employees or officials who are not in accordance with their qualifications, competencies, and performance. In the Bogor City Government this is also an problems faced in job placement that lead to ineffective and inefficient organizational achievements. The research method that the author uses is descriptive qualitative using George C Edward III theory which focuses on important variables in the successful implementation of the program, namely, Size and Objectives, Resources, and, the Anjas Go Clear Model itself and is supported by triangulation theory to strengthen data. The results of this study indicate that the innovation of Anjas Go Clear (Nomative Application for Government Clear Structural Position) in Bogor City has gone well in placing employees according to organizational needs. So that the goal of placing employees in accordance with their qualifications, competence, and performance without political intervention from stakeholders can be achieved. The most profound obstacle is the data security aspect of the lack of data security to ensure the confidentiality of the draft structural appointment structure.